Revitalizing a Traditional Game “Dakon” to Teach English for Young Learners - Femi Eka Rahmawati; Esti Junining (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2018)
A traditional game can develop either cognitive, social or emotional skills of the children. Dakon, one of the name of traditional game from Java, becomes the point of discussion in this paper. Dakon is made of wood or plastic with fourteen pits filled with particles like tamarine seeds, snail cover or small stones. This game can be played by two players facing each other by filling the particles to each pit. In the last stopped stone, the student should see the letter printed in the pit and then start spelling the letter, pronounce the word and read the usage of the word in a simple sentence provided. This part is played again and again until the particles are empty. This paper aims at designing a traditional game, dakon, to learn pronunciation and vocabulary. This game is designed for young learners (elementary school students) who willingly learn English in pairs. Besides learning English, this game also can develop the learners’ social interaction with friends at similar ages. This is a Design Based Research by designing art concept. The result shows that the Elementary school students enjoy learning English using this game.